Alphaworld: robots: teacher edition - Rees, Rod (Oxford University Press Melbourne, 2004)
"Robots" is an engaging exploration of the world of robotics, aimed at introducing readers to the various types of robots and their functions. The book delves into how robots are used in different fields, such as manufacturing, healthcare, and space exploration, highlighting their capabilities and the technology behind them. It explains complex concepts in an accessible way, often using vivid illustrations and relatable examples to capture the imagination of young readers.